Plant extracts and commercial products for controlling black spot and inducing resistance in rose bushes - Simon, Janaina Myashiro; Alencar, Mariana Santos Rodrigues; Oliveira, Juliana Batista; Schwan-Estrada, Katia Regina Freitas; Jardinetti, Virlene do Amaral; Maia, Aline (Comunicata Scientiae, 2024)
Rose is one of the most appreciated flowers in the world; however, fungal diseases can affect its production, decreasing its commercial value. Thus, the objective of this work was to assess the potential of extracts of medicinal plants and commercial products based on plant extracts, plant oils, and potassium phosphite to control black spot (Diplocarpon rosae) in roses by evaluating the activation of plant defense mechanisms. The treatments consisted of using crude aqueous extract (CAE) of Rosmarinus officinalis leaves; CAE of Equisetum arvense stems; CAE of Moringa oleifera seeds; commercial product (CP) based on fermented plant extracts; CP based on potassium phosphite; CP based on plant oils; CP based on citrus mass; and fungicide. Severity of black spot disease, and yield, biometry, chlorophyll contents, and enzyme activity of peroxidase, catalase, and polyphenoloxidase in rose plants were evaluated. The treatments presented no difference from the control (water) for disease incidence and severity and yield. However, the longest stem was found in rose plants in the treatment with potassium phosphite-based commercial product, whereas the thickest stems were found in the three treatments with commercial products. The highest enzyme specific activities of peroxidase, catalase, and polyphenoloxidase were found in plants treated with potassium phosphite, CAE of M. oleifera, and CAE of R. officinalis. The results found showed that the tested natural products did not control black spot in rose bushes, despite their positive effect on plant physiology.